2019
DOI: 10.1371/journal.pone.0213028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling simulation studies reveal new potential inhibitors against HPV E6 protein

Abstract: High-risk strains of human papillomavirus (HPV) have been identified as the etiologic agent of some anogenital tract, head, and neck cancers. Although prophylactic HPV vaccines have been approved; it is still necessary a drug-based treatment against the infection and its oncogenic effects. The E6 oncoprotein is one of the most studied therapeutic targets of HPV, it has been identified as a key factor in cell immortalization and tumor progression in HPV-positive cells. E6 can promote the degradation of p53, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The application of ED to analyze protein behaviour mainly focuses on the dominant modes of motion, which are obtained by decomposing the covariance matrix and by ranking the eigenvectors (principal components) in descending order of the corresponding eigenvalues [292,332]. By plotting the first two or three principal components against each other, we obtain a general idea of the distribution for all generated conformations obtained from a conformational sampling experiment, as exemplified from ED analyzes for various proteins [333][334][335][336]. On the resulting figure, one may obtain conformationally distinct clusters of the simulated proteins or complexes.…”
Section: Essential Dynamics and Free-energy Landscapementioning
confidence: 99%
“…The application of ED to analyze protein behaviour mainly focuses on the dominant modes of motion, which are obtained by decomposing the covariance matrix and by ranking the eigenvectors (principal components) in descending order of the corresponding eigenvalues [292,332]. By plotting the first two or three principal components against each other, we obtain a general idea of the distribution for all generated conformations obtained from a conformational sampling experiment, as exemplified from ED analyzes for various proteins [333][334][335][336]. On the resulting figure, one may obtain conformationally distinct clusters of the simulated proteins or complexes.…”
Section: Essential Dynamics and Free-energy Landscapementioning
confidence: 99%
“…Using 26 reference compounds, mostly flavonoids, known to inhibit E6, this group created a large compound library based on structural similarity to the references, and then utilized docking screening and molecular dynamic simulations to virtually screen and validate the hits. They identified three novel compounds, lig1, 2, and 3 [ 65 ]. However, follow-up experiments to validate p53 rescue or apoptosis induction in HPV + cells are still pending.…”
Section: Therapeutic Targeting Of E6 Ppismentioning
confidence: 99%
“…Flavanoid compounds, Luteolin and CAF024, which mimic leucines in the conserved alpha helical motif of E6AP have been found to inhibit the E6–E6AP interaction [ 134 ]. Molecular modelling and simulation studies have revealed some additional inhibitors of the E6–E6AP interaction [ 135 ]. It has been demonstrated that the space between the two Zinc finger domains of E6 constitutes the LxxLL binding pocket [ 136 ].…”
Section: Therapeutic Approaches To Target E6ap and Downstream Effementioning
confidence: 99%